2005
DOI: 10.1111/j.0013-0427.2005.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

Worker Reciprocity and Employer Investment in Training

Abstract: Standard economic theory predicts that firms will not invest in general training and will underinvest in specific training. Empirical evidence, however, indicates that firms do invest in general training of their workers. Evidence from laboratory experiments points to less underinvestment in specific training than theory predicts. We propose a simple model in which a firm invests the socially optimal amounts in general and specific training if the worker is sufficiently motivated by reciprocity. A reciprocal w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 23 publications
1
53
0
1
Order By: Relevance
“…There is of course no guarantee that this is the case. 13 In a related paper, Leuven et al (2004) showed that worker reciprocity can play a similar role as firm reputation in improving investment incentives for the other (investing) party.…”
Section: Hold-upmentioning
confidence: 99%
“…There is of course no guarantee that this is the case. 13 In a related paper, Leuven et al (2004) showed that worker reciprocity can play a similar role as firm reputation in improving investment incentives for the other (investing) party.…”
Section: Hold-upmentioning
confidence: 99%
“…12 Leuven et al (2005) are among the first investigators to introduce reciprocity in the empirical training literature. They base their definition of reciprocity on that of Fehr and Gächter (2000), who define it as an individual's response to a friendly action as "frequently much nicer and much more cooperative than predicted by the self-interested model" (p.…”
Section: Iib Personality Traits and Training Participationmentioning
confidence: 99%
“…In particular, Leuven et al (2005) showed that positive reciprocal inclinations of employees are critical to explaining why employers are willing to provide firm-specific as well as general training to their employees. 25 Their argument is that training positively affects the knowledge, skills and productivity of individual employees, who may therefore perceive the willingness of their employer to offer training opportunities and to pay for both firm-specific and general training as a gift, or as a signal of attention and recognition by the employer, for which they first take the arithmetic average of a respondent's answers to these three questions, and compute the sample median value.…”
Section: Positive Reciprocitymentioning
confidence: 99%
“…The role of reciprocal behavior by employees in relation to the human capital investments by their employer, however, is a relatively unexplored topic. A notable exception is Leuven et al (2005), who applied a gift-exchange framework to explain why employers are willing to provide both firm-specific and general training to their employees. Their argument is similar to that of the efficiency-wage literature, which predicts that higher effort levels can be achieved when employers pay wages above the market-clearing wage (Akerlof, 1982).…”
mentioning
confidence: 99%